The pathogen causing Dutch elm disease makes host trees attract insect vectors. - McLeod, Geoff; Gries, Regine; Von Reuss, Stephan; Rahe, James E; McIntosh, Rory; König, Wilfried A; Gries, Gerhard (My University, 2005)
Dutch elm disease is caused by the fungal pathogen Ophiostoma novo-ulmi which is transmitted by the native elm bark beetle, Hylurgopinus rufipes. We have found that four semiochemicals (the monoterpene (-)-beta-pinene and the sesquiterpenes (-)-alpha-cubebene, (+)-spiroaxa-5,7-diene and (+)-delta-cadinene) from diseased American elms, Ulmus americana, synergistically attract H. rufipes, and that sesquiterpene emission is upregulated in elm trees inoculated with O. novo-ulmi. The fungus thus manipulates host trees to enhance their apparency to foraging beetles, a strategy that increases the probability of transportation of the pathogen to new hosts.